Investigations on the effects of scatterers on the MIMO channel characteristics in LOS environment - LIU Lei-lei; HONG Wei (Tongxin xuebao)
The effects of scattering objects on MIMO（multiple input multiple output） channel characteristics in line-of-sight（LOS） environment were investigated.The study was focused on the outdoor LOS environment but with a scatterer.The analytical mathematical expressions were derived to describe the MIMO channel matrix,where the microstrip an-tennas and 2-D cylindrical scatterer were considered.The MIMO channel capacity and the condition number of the ma-trix were investigated.From the simulation results of the MIMO channel characteristics of the model,some suggestions for practical MIMO system design are proposed.